2019
DOI: 10.3389/fchem.2019.00862
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic Metal Complexes of a Pyrimidinyl Based Schiff Base Ligand Incorporating 2,2′-Bipyridine Moiety: Synthesis, Characterization, and Biological Studies

Abstract: A sequence of transition metal complexes of Mn(II), Co(II), Ni(II), and Cu(II) incorporating a novel pyrimidinyl based Schiff base ligand, 2-(4,6-dimethylpyrimidin-2-ylamino)naphthalene-1,4-dione (HL) and 2,2 ′-bipyridine has been synthesized and characterized using elemental, magnetic, conductance, infrared (FT-IR), nuclear magnetic resonance (1 Hand 13 C-NMR), electronic (UV-Vis), electrospray ionization mass spectrometry (ESI-MS), thermographic analysis (TGA), and molecular docking studies. The acquired res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…For this study, they seeded 0.2 mL of 24 h grown microbial culture in each plate and bore wells with the sterile cork of 7 mm diameter and introduced the tested samples prepared at 10 mg/mL concentration in DMSO. The study revealed moderate to some very good antimicrobial activity, even surpassing the control drug's activity several times [52]. The antioxidant capacity of all the synthesized complexes was good and the ligand showed even better activity than the standard ascorbic acid. )…”
Section: Chemotherapeutic Applicationsmentioning
confidence: 78%
See 1 more Smart Citation
“…For this study, they seeded 0.2 mL of 24 h grown microbial culture in each plate and bore wells with the sterile cork of 7 mm diameter and introduced the tested samples prepared at 10 mg/mL concentration in DMSO. The study revealed moderate to some very good antimicrobial activity, even surpassing the control drug's activity several times [52]. The antioxidant capacity of all the synthesized complexes was good and the ligand showed even better activity than the standard ascorbic acid. )…”
Section: Chemotherapeutic Applicationsmentioning
confidence: 78%
“…Heteroleptic metal complexes of pyrimidinyl-based Schiff base ligand also possess good antimicrobial activity against various pathogenic bacteria and fungi. In a previous study, Festus et al (2019) synthesized Mn(II), Co(II), Ni(II), and Cu(II) complexes of novel Schiff base ligand (23) (2-(4,6dimethylpyrimidin-2-ylamino)naphthalene-1,4dione and 2,2′-bipyridine) and appraised them antimicrobial evaluation against S. aureus, E. coli, P. aeruginosa, B. cereus, P. mirabilis, K. oxytoca, A. niger, A. flevus, and R. stolonifer organisms following the agar-well diffusion method. For this study, they seeded 0.2 mL of 24 h grown microbial culture in each plate and bore wells with the sterile cork of 7 mm diameter and introduced the tested samples prepared at 10 mg/mL concentration in DMSO.…”
Section: Chemotherapeutic Applicationsmentioning
confidence: 86%
“…Furthermore, NiL 1 Gly, CoL 3 Gly, NiL 3 Gly demonstrated much-enhanced susceptibility as compared to ligands and glycine against B. cereus . These improved antibacterial activities of complexes may be attributed to the involvement of hyper-conjugation and induction of greater lipo solubility [ 22 ]. The polarity of metal ions diminished and caused delocalization of π-electrons, which, in turn, favored the penetration of complexes through the bacterial membrane, subsequently enhancing their activity [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on antibacterial activity of synthesized ligands and metal complexes were performed with slight changes in the reported protocol [ 22 ]. Six microbial strains viz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation